Patients Walking Faster After Anterior Cruciate Ligament Reconstruction Have More Gait Asymmetry - Rachel J. Knobel; Naoaki Ito; Elanna K. Arhos; Jacob J. Capin; Thomas S. Buchanan; Lynn Snyder-Mackler (North American Sports Medicine Institute, 2021)
# Background Gait asymmetries after anterior cruciate ligament reconstruction (ACLR) may lead to radiographic knee osteoarthritis. Slower walking speeds have been associated with biomarkers suggesting cartilage breakdown. The relationship between walking speed and gait symmetry after ACLR is unknown. # Hypothesis/Purpose To determine the relationship between self-selected walking speeds and gait symmetry in athletes after primary, unilateral ACLR. # Study Design Secondary analysis of a clinical trial. # Methods Athletes 24±8 weeks after primary ACLR walked at self-selected speeds as kinematics, kinetics, and electromyography data were collected. An EMG-driven musculoskeletal model was used to calculate peak medial compartment contact force (pMCCF). Variables of interest were peak knee flexion moment (pKFM) and angle (pKFA), knee flexion and extension (KEE) excursions, peak knee adduction moment (pKAM), and pMCCF. Univariate correlations were run for walking speed and each variable in the ACLR knee, contralateral knee, and interlimb difference (ILD). # Results Weak to moderate positive correlations were observed for walking speed and all variables of interest in the contralateral knee (Pearson's r=.301-.505, p≤0.01). In the ACLR knee, weak positive correlations were observed for only pKFM (r=.280, p=0.02) and pKFA (r=.263, p=0.03). Weak negative correlations were found for ILDs in pKFM (r=-0.248, p=0.04), KEE (r=-.260, p=0.03), pKAM (r=-.323, p<0.01), and pMCCF (r=-.286, p=0.02). # Conclusion Those who walk faster after ACLR have more asymmetries, which are associated with the development of early OA. This data suggests that interventions that solely increase walking speed may accentuate gait symmetry in athletes early after ACLR. Gait-specific, unilateral, neuromuscular interventions for the ACLR knee may be needed to target gait asymmetries after ACLR. # Level of Evidence III